(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Brushless DC (BLDC) motors are preferred as small horse power control motors due to their high efficiency, silent operation, compact form, reliability, and low maintenance but suffer from problem on operation at variable speed so need a precise controller to be designed. Usually in these motors speed control is achieved by using proportional-integral-derivative (PID) controller being simple in structure but PID controllers require precise linear mathematical models. A new algorithms-specific variable less optimization technique has been applied and results are compared with Zieglar-Nichols based PID controller